Discursos de ódio no facebook: uma experiência ética a partir das reações a publicações sobre adolescentes que cometem atos infracionais - Weidson Leles Gomes (2019)
The present study aims to problematize the ethical conduct of the subject who reacts with hate speech to posts on Facebook about adolescents who commit infractions. For its development, the research will articulate procedures of the genealogy of the ethics of Foucault, of the netnography, of the analysis of social networks and of the case study. The research problem of the present study is: which is the ethical conduct of the subject who, on Facebook, reacts with a hate speech to posts about adolescents who commit infractions? It is hypothesized that there is a hate speech (BRUGGER, 2007) that propagates a notion of the adolescent as a "minor", as delinquent, arguing that social networks have opened a perverse side of the human. Discourses seek to produce an "other" to be exterminated, punished, devoid of humanity, demonized. This work can contribute to a deeper reflection on the functioning of hate in digital social networks. The goal of the product is to contribute to the training of servers of the Socio-educational System and education professionals. There are short videos created with "Vyond" using techniques such as storyboarding. The tutorial for the video creation process will be shared as an Open Educational Resource with Creative Commons license, contributing to the training of socio-educational security agents, technical staff, teachers and interested in the use of instructional design tools and Vyond.